Revisiting the Role of ß-Tubulin in Drosophila Development: β-tubulin60D is not an Essential Gene, and its Novel Pin1 Allele has a Tissue-Specific Dominant-Negative Impact - Krishnan, Ramesh Kumar; Halachmi, Naomi; Baskar, Raju; Bakhrat, Anna; Zarivach, Raz; Salzberg, Adi; Abdu, Uri (Frontiers in Cell and Developmental Biology, 2022)
Diversity in cytoskeleton organization and function may be achieved through alternative tubulin isotypes and by a variety of post-translational modifications. The Drosophila genome contains five different β-tubulin paralogs, which may play an isotype tissue-specific function in vivo. One of these genes, the β-tubulin60D gene, which is expressed in a tissue-specific manner, was found to be essential for fly viability and fertility. To further understand the role of the β-tubulin60D gene, we generated new β-tubulin60D null alleles (β-tubulin60DM) using the CRISPR/Cas9 system and found that the homozygous flies were viable and fertile. Moreover, using a combination of genetic complementation tests, rescue experiments, and cell biology analyses, we identified Pin1, an unknown dominant mutant with bristle developmental defects, as a dominant-negative allele of β-tubulin60D. We also found a missense mutation in the Pin1 mutant that results in an amino acid replacement from the highly conserved glutamate at position 75 to lysine (E75K). Analyzing the ß-tubulin structure suggests that this E75K alteration destabilizes the alpha-helix structure and may also alter the GTP-Mg2+ complex binding capabilities. Our results revisited the credence that β-tubulin60D is required for fly viability and revealed for the first time in Drosophila, a novel dominant-negative function of missense β-tubulin60D mutation in bristle morphogenesis.